KNOWLEDGE, ATTITUDES TO, AND UTILIZATION OF THE NATIONAL HEALTH INSURANCE SCHEME (NHIS) AMONG HEALTH WORKERS IN THE UNIVERSITY OF NIGERIA TEACHING HOSPITAL(UNTH), ITUKU-OZALLA, ENUGU STATE, NIGERIA - Celestine E, Ekwuluo; Achama N, Eluwa; Isaac C, Okereke; Somtochukwu B, Orji (International Journal of Research -GRANTHAALAYAH, 2018)
This is a study to determine the knowledge, attitudes to, and utilization of the National Health Insurance Scheme (NHIS) among health workers at the University of Nigeria Teaching Hospital (UNTH), Ituku-Ozalla, and Enugu State, Nigeria. It is a descriptive study. Information was gathered using a closely monitored interviewer-administered questionnaire. Method: A stratified random sampling method in which 328 questionnaires were satisfactory completed, was carried out in December 2011 at the University of Nigeria, Teaching Hospital, Ituku-Ozalla. The questionnaires used in this study were a combination of both structured close-ended questions and unstructured open-ended questions. The data was analyzed using statistical program for social sciences (SPSS) software. Variables explored in our study were aimed at understanding the factors affecting and recommending ways of improving the knowledge, utilization of, and attitude to the National Health Insurance Scheme (NHIS) among health workers at the University of Nigeria Teaching Hospital (UNTH), Ituku-Ozalla, Enugu State, Nigeria,. Results: 188 (57.3%) of our respondent were females, while 140 (42.7%) were males. There was a 98.2% awareness among the respondents as against 1.8% who had not heard of the scheme prior to this research. About 36.3% of respondents had heard of the scheme from colleagues, 37.3% from the radio/television, while only 3.7% had gotten their information about the NHIS from the internet. 63.4% of the respondents were registered beneficiaries of the NHIS as against 36.6% who were not registered. An encouraging 70.1% of the registered respondents had actually used the scheme before. Important to note was that 41.1% of registered married respondents had actually utilized the scheme while only 39.5% of the registered single respondents were indeed users. From the research, there is a low patronage of the scheme by doctors as only 41.1% of the doctors were registered as against 60.3% of nurses, 100% of financial officers and 84.2% of the support workers that were registered. Conclusion: 65.7% of the respondent believed that the scheme was not expensive, while only about 16.7% of the respondents wanted the scheme discontinued. Generally there is a high awareness of the National Health Insurance Scheme. However, the utilization of, and attitudes to the National Health Insurance Scheme are not encouraging. Respondents were optimistic about the scheme as majority felt it should be improved on rather than discontinued. Providing solution to the problems and limitations highlighted in our study will go a long way in improving the health and wellbeing of the health workers and by extension, the entire populace in a country like Nigeria.